Smoke dispersion modeling over complex terrain using high resolution meteorological data and satellite observations – The FireHub platform. (October 2015) - Solomos, S.; Amiridis, V.; Zanis, P.; Gerasopoulos, E.; Sofiou, F.I.; Herekakis, T.; Brioude, J.; Stohl, A.; Kahn, R.A.; Kontoes, C.
Abstract: A total number of 20, 212 fire hot spots were recorded by the Moderate Resolution Imaging Spectroradiometer (MODIS) satellite instrument over Greece during the period 2002–2013. The Fire Radiative Power (FRP) of these events ranged from 10 up to 6000 MW at 1 km resolution, and many of these fire episodes resulted in long-range transport of smoke over distances up to several hundred kilometers. Three different smoke episodes over Greece are analyzed here using real time hot-spot observations from the Spinning Enhanced Visible and Infrared Imager (SEVIRI) satellite instrument as well as from MODIS hot-spots. Simulations of smoke dispersion are performed with the FLEXPART-WRF model and particulate matter emissions are calculated directly from the observed FRP. The modeled smoke plumes are compared with smoke stereo-heights from the Multiangle Imaging Spectroradiometer (MISR) instrument and the sensitivities to atmospheric and modeling parameters are examined. Driving the simulations with high resolution meteorology (4 × 4 km) and using geostationary satellite data to identify the hot spots allows the description of local scale features that govern smoke dispersion. The long-range transport of smoke is found to be favored over the complex coastline environment of Greece due to the abrupt changes between land and marine planetary boundary layers (PBL) and the decoupling of smoke layers from the surface. Highlights: A synergistic satellite-modeling approach is proposed for biomass smoke forecasts. FLEXPART-WRF model allows the description of biomass dispersion at local scale. Satellite data (MISR, MODIS, SEVIRI) are used to constrain and evaluate the model. Interchange between marine and land PBL affects smoke plume properties. Satellite FRP is necessary for the top-down estimation of emissions and plume rise.